„MOȘTENIT DIN SUBSTRAT, PÂNĂ LA URMĂ”. REFLECȚII PE MARGINEA UNUI DICȚIONAR: “INHERITED FROM THE SUBSTRATUM, ULTIMATELY”. REFLECTIONS ON A DICTIONARY (Theoretical and Applied Linguistics@ro, 2025)
In this study, I analyse a recently published etymological dictionary of the Romanian language. My focus is on the structure of the dictionary, the method followed by the lexicographer and the criteria – phonetic, onomasiological and derivational – used tocategorise terms within the Dacian substratum of the Romanian language. The author of the dictionary believes that many words with unknown etymologies in the DEX (Explanatory Dictionary of the Romanian Language) belong to the substratum. However, this group ofwords is not the only source of the increase in the number of words presumed to originate from the substratum. The author takes a fresh look at many words that are currently considered to be of Slavic, Hungarian, Turkish or Latin origin, and consistently links common lexical terms to toponyms and anthroponyms that share Indo-European roots. The present study compares the etymological solutions proposed in this dictionary with those generally accepted by other etymological studies and the best Romanian dictionaries. The author of the dictionary considers that approximately 1,500 words have been inherited from the substratum, which is ten times higher than the figure arrived at in previous studies by other authors. The same author also considers that various elements of morphology, such as the definite and indefinite articles and the auxiliary verbs used to form the present perfect, future and conditional, come from the substratum. It can therefore be concluded that this etymological dictionary is a work of fiction rather than a serious piece of lexicography.
Keywords: etymological dictionary; Romanian substratum; fringe theory; Dacianism